Formation Features of the Enterprises Investment Policy in the Context of Global Shifts - Anhelko, Iryna (Journal of Vasyl Stefanyk Precarpathian National University, 2024)
The article highlights the main aspects of the formation of the investment policy of enterprises in the conditions of global changes. Attention is focused on the need to analyze the sources of investment financing, determine their volume, structure and relationship with the investment activity of economic entities. Based on the analysis of official data, it was established that in the structure of investment financing sources, the own funds of enterprises and organizations prevail. It is noted that the quantitative composition of investments directly affects the investment activity of business entities. The method of factor analysis was used to identify the relationship between the volume of investments and the level of investment activity of economic entities. Official data from the State Statistics Service of Ukraine on the total volume of capital investments and performance indicators of business entities for 2017-2021 were used to conduct the above analysis. It was established that the level of investment activity of Ukrainian business entities is low. It is summarized that the low level of investment activity of business entities is associated with a number of problems, including the ineffective investment policy of business entities. The author's model of the formation of an effective investment policy of enterprises in terms of its main stages, functions and tasks is proposed. At the same time, it is stated that the formation of an investment policy by a separate business entity allows it to economically justify the feasibility, terms, volume of investment, and determine the required volume and types of resources. In turn, the effective implementation of the enterprise's investment policy affects the increase of its investment activity. However, despite the effectiveness and clarity of the formation of the investment policy, it must be regularly reviewed and, if necessary, adjusted, because in the conditions of global changes, the external environment is quite changeable and unpredictable.